An improved understanding of the roles of atomic processes and power balance in divertor target ion current loss during detachment. (17th October 2019) - Verhaegh, K.; Lipschultz, B.; Duval, B.P.; Février, O.; Fil, A.; Theiler, C.; Wensing, M.; Bowman, C.; Gahle, D.S.; Harrison, J.R.; Labit, B.; Marini, C.; et al.
Abstract: The process of divertor detachment, whereby heat and particle fluxes to divertor surfaces are strongly diminished, is required to reduce heat loading and erosion in a magnetic fusion reactor to acceptable levels. In this paper, the physics leading to the decrease of the total divertor ion current ( I t ), or 'roll-over', is experimentally explored on the TCV tokamak through characterization of the location, magnitude and role of the various divertor ion sinks and sources including a complete analysis of particle and power balance. These first measurements of the profiles of divertor ionisation and hydrogenic radiation along the divertor leg are enabled through novel spectroscopic techniques. Over a range in TCV plasma conditions (plasma current and electron density, with/without impurity-seeding) the I t roll-over is ascribed to a drop in the divertor ion source; recombination remains small or negligible farther into the detachment process. The ion source reduction is driven by both a reduction in the power available for ionization, P recl, and concurrent increase in the energy required per ionisation, E ion : this effect of power available on the ionization source is often described as 'power starvation' (or 'power limitation'). The detachment threshold is found experimentally (in agreement with analytic model predictions) to be P recl / I t E ion 2, corresponding to a target electron temperature, T t E ion / γ where γ is the sheath transmission coefficient. The target pressure reduction, required to reduce the target ion current, is driven both by volumetric momentum loss as well as upstream pressure loss. The measured evolution through detachment of the divertor profile of various ion sources/sinks as well as power losses are quantitatively reproduced through full 2D SOLPS modelling through the detachment process as the upstream density is varied.